2014
DOI: 10.1177/0021886314532945
|View full text |Cite
|
Sign up to set email alerts
|

Five Configurations for Scaling Up Social Innovation

Abstract: Why do so many social innovations fail to have a broad impact? Successful social entrepreneurs and nonprofit organizations often “scale out” innovative solutions to local problems in order to affect more communities or numbers of individuals. When faced with institutional barriers, they are motivated to “scale up” their efforts to challenge the broader institutional rules that created the problem. In doing so, they must reorient their own and their organizations’ strategies, becoming institutional entrepreneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(87 citation statements)
references
References 14 publications
0
58
0
3
Order By: Relevance
“…These differences between social entrepreneurs were also found by Westley et al (2014), who identified social entrepreneurs who develop and scale their social innovations based on an inclusive and participatory process, whereby stakeholders have a direct voice regarding the social innovation, in contrast to social entrepreneurs who develop and scale their social innovations based on their own strong vision. The latter succeeded due to their consistency and drive without compromising their initially chosen vision and priorities (Westley et al 2014). Table 7 summarizes the key similarities and differences between the four identified approaches to develop innovative solutions for societal problems.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These differences between social entrepreneurs were also found by Westley et al (2014), who identified social entrepreneurs who develop and scale their social innovations based on an inclusive and participatory process, whereby stakeholders have a direct voice regarding the social innovation, in contrast to social entrepreneurs who develop and scale their social innovations based on their own strong vision. The latter succeeded due to their consistency and drive without compromising their initially chosen vision and priorities (Westley et al 2014). Table 7 summarizes the key similarities and differences between the four identified approaches to develop innovative solutions for societal problems.…”
Section: Discussionmentioning
confidence: 86%
“…However, the innovative solution may also induce or require social change processes, especially in cases where social entrepreneurs need to challenge the social systems that created the problems they address. In those cases, social entrepreneurs turn into institutional entrepreneurs and act as change agents in society (Westley et al 2014). This understanding resonates with the social constructionists who aim to mend social fabrics, or social engineers who introduce effective new social systems to replace former systems that are ill-equipped to address social needs (Zahra et al 2009).…”
Section: Social Innovationmentioning
confidence: 87%
“…Do we need to be more creative in devising scaling strategies? We may, for example, need to choose to focus more on creating conditions for scaling rather than on actively trying to make something go to scale (Leeuwis and Aarts 2012;Westley et al 2014;Wigboldus and Leeuwis 2013). It may also involve considering a range of potential leverage points (entry points) in terms of places to intervene in systems (Meadows 2009).…”
Section: Conclusion: Current Contribution Of Promis and Next Stepsmentioning
confidence: 99%
“…Scaling out captures what happens when a project or organization is grown so that it serves more people over a larger area. The extensive dimension, or what Westley and colleagues would term scaling up, happens when individual projects grow so they achieve critical mass to either provide a service to all people or are able to bring about institutional and/or structural change Westley et al, 2011).…”
Section: Future Research Directionsmentioning
confidence: 99%